2015
DOI: 10.3390/nu7043000
|View full text |Cite
|
Sign up to set email alerts
|

Height, Zinc and Soil-Transmitted Helminth Infections in Schoolchildren: A Study in Cuba and Cambodia

Abstract: Soil-transmitted helminth (STH) infections and zinc deficiency are often found in low- and middle-income countries and are both known to affect child growth. However, studies combining data on zinc and STH are lacking. In two studies in schoolchildren in Cuba and Cambodia, we collected data on height, STH infection and zinc concentration in either plasma (Cambodia) or hair (Cuba). We analyzed whether STH and/or zinc were associated with height for age z-scores and whether STH and zinc were associated. In Cuba,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 36 publications
(40 reference statements)
0
17
0
2
Order By: Relevance
“…For instance, Sanchez et al,34 found no association between STH and IL‐10 in a study in Honduran children. Also, de Gier et al35, did not find differences in acute phase protein or CRP in Cuban or Cambodian children between infected and non‐infected children with STH. Our results confirm the lack of association between systemic inflammatory markers and intestinal parasitic infection.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…For instance, Sanchez et al,34 found no association between STH and IL‐10 in a study in Honduran children. Also, de Gier et al35, did not find differences in acute phase protein or CRP in Cuban or Cambodian children between infected and non‐infected children with STH. Our results confirm the lack of association between systemic inflammatory markers and intestinal parasitic infection.…”
Section: Discussionmentioning
confidence: 89%
“…33 For instance, Sanchez et al, 34 found no association between STH and IL-10 in a study in Honduran children. Also, de Gier et al 35 To our knowledge, this is the first study to evaluate the relation-…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Hair has the advantage of being easily collected and is stable indefinitely if stored appropriately. Included studies collected hair samples ranging from 0.2 to 2g, from the nape of the neck, adjacent to scalp (4, 6), or from 1.5 cm from scalp at the nape or occipital region (5). Hair samples were washed in deionised water, dried and acid digested prior to analysis by either atomic absorption spectrometry (AAS) (4,5) or inductively couple plasma mass spectrometry (ICPMS) (6).…”
Section: Hair [Zn]mentioning
confidence: 99%